Chitosan based nanocomposite films and coatings: Emerging antimicrobial food packaging alternatives. (March 2020) - Kumar, Santosh; Mukherjee, Avik; Dutta, Joydeep
Abstract: Background: Demand for healthy and safe food with minimal use of synthetic inputs (including synthetic preservatives) is increasing rapidly. Plastic polymers being hazardous to the environment, significant efforts have been devoted to evaluate various bio-based polymers as alternatives to synthetic plastic packaging. Chitin and its deacetylated derivative, chitosan, is primarily a by-product of crustacean, fish and seafood processing and handling. Chitosan possesses antimicrobial activities and film forming property, making them attractive biopolymers for food packaging and food preservation applications applied through spraying, dipping, coating, or wrapping by films. Scope and approach: This comprehensive review of contemporary research focuses on applications of chitosan and chitosan based nanocomposites in the area of food packaging and preservation. It includes different properties and functionalities of chitosan, various blends and nanocomposites of chitosan, their fabrication techniques, and applications in shelf life extension of fruits, vegetables, meat and fish products. Key findings and conclusions: Chitosan is an attractive alternative to synthetic plastics polymers due to its biodegradability, antimicrobial activity, and film forming properties. Incorporation of nanomaterials into chitosan based food-packaging systems can prevent the growth of spoilage and pathogenic microorganisms, improve food quality and safety, and extend shelf-life of food. It has been reported that applications of chitosan-based films or coatings or treatments have resulted in shelf life extension of fresh produce, meat products, bread, and dairy products such as cheese which has been highlighted. Highlights: Consumers demand for healthy and safe food with minimal synthetic inputs. Chitosan is an antimicrobial biopolymer derived from fish processing wastes. Chitosan has been effectively used in food packaging applications. Chitosan film or coating or treatment enhances shelf life of perishable food. Chitosan nanocomposites are emerging antimicrobial food packaging alternatives.